Recurrence risks to sibs of MS index cases: impact of consanguineous matings. - Dessa Sadovnick, A; Yee, I; Ebers, G (2001)
Using population-based data, the authors identified 24 MS index cases whose parents were related. Twenty-two had 67 sibs of whom 6 also had MS, yielding a recurrence risk of approximately 9%, significantly higher than for sibs of MS index cases from nonconsanguineous parents. These findings support the concept that multiple interacting genes increase the risk of MS.